Decisional conflict among couples seeking specialty treatment for infertility in the USA: a longitudinal exploratory study. Issue 3 (10th March 2020) - Anguzu, R; Cusatis, R; Fergestrom, N; Cooper, A; Schoyer, K D; Davis, J B; Sandlow, J; Flynn, K E
Abstract: STUDY QUESTION: What are couples' decisional conflicts around family-building approaches before and after seeking a specialty consultation for infertility? SUMMARY ANSWER: Decisional conflict is high among couples before an initial specialty consultation for infertility; on average, women resolved decisional conflict more quickly than men. WHAT IS KNOWN ALREADY: Couples have multiple options for addressing infertility, and decisional conflict may arise due to lack of information, uncertainty about options and potential risks or challenges to personal values. STUDY DESIGN, SIZE, DURATION: We conducted a total of 385 interviews and 405 surveys for this longitudinal, mixed-methods cohort study of 34 opposite-sex couples who sought a new reproductive specialty consultation ( n  = 68), who enrolled before the initial consultation and were followed over 12 months. PARTICIPANTS/MATERIALS, SETTING, METHODS: The in-depth, semi-structured interviews included questions about information gathering, deliberation and decision-making, and self-administered surveys included the Decisional Conflict Scale (DCS), at six time points over 12 months. A DCS total score of 25 is associated with implementing a decision, and higher scores indicate more decisional conflict. A systematic content analysis of interview transcripts identified major themes. Paired t tests identified differences in DCS between women and men within couples. Linear mixed models predicted changes in DCS over time, adjusting for sociodemographic and fertility-related factors. MAIN RESULTS AND THE ROLE OF CHANCE: The major qualitative themes were communication with partners, feeling supported and/or pressured in decision (s), changing decisions over time and ability to execute a desired decision. Average DCS scores were highest before the initial consultation. Within couples, men had significantly higher decisional conflict than women pre-consultation (48.9 versus 40.2, P  = 0.037) and at 2 months (28.9 versus 22.1, P  = 0.015), but differences at other time points were not significant. In adjusted models, predicted DCS scores declined over time, with women, on average, reaching the DCS threshold for implementing a decision at 2 months while for men it was not until 4 months. LIMITATIONS, REASONS FOR CAUTION: This is a convenience sample from a single center, and generalizability may be limited. WIDER IMPLICATIONS OF THE FINDINGS: Understanding how couples discuss and make decisions regarding family-building could improve the delivery of patient-centered infertility care. Our findings are the first to prospectively explore decisional conflict at multiple time points in both men and women; the observed gender differences underlie the importance of supporting both partners in clinical decision-making for infertility. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the National Institute of Child Health and Human Development under Grant [R21HD071332], the Research and Education Program Fund, of the Advancing a Healthier Wisconsin endowment at Medical College of Wisconsin, the National Research Service Award under Grant [T32 HP10030] and the use of REDCap for data collection from the National Center for Advancing Translational Sciences, National Institutes of Health under Grant through [8UL1TR000055]. The authors have no competing interests.